Developing Nitrogen Isotopic Source Profiles of Atmospheric Ammonia for Source Apportionment of Ammonia in Urban Beijing - Wang, Chenjing; Li, Xiujuan; Zhang, Tianle; Tang, Aohan; Cui, Min; Liu, Xuejun; Ma, Xin; Zhang, Yangyang; Liu, Xiaomeng; Zheng, Mei (Frontiers in Environmental Science, 2022)
Atmospheric ammonia (NH3) is the key precursor in secondary particle formation, which is identified as the most abundant components of haze in Beijing in most cases. It is critical to understand the characteristics of NH3 from various emission sources and quantify each source contribution to NH3 in ambient atmosphere. Stable nitrogen (N) isotope composition (δ15N) is an effective tool to study NH3 source. However, this tool cannot be effectively applied in Beijing due to the lack of comprehensive N nitrogen isotope source profiles. Reliable source profiles are the basis of source apportionment of NH3 using the isotope mixing model. In this study, multiple NH3 source samples were collected at sites representing six major NH3 source types in Beijing from 2017 to 2018 in four seasons. δ15N values of 212 NH3 source samples were determined to build local source profiles database of δ15N. NH3 from traffic source presents significantly higher δ15N values (-14.0 ± 5.4‰), distinguished from other sources. The δ15N values of other sources besides traffic were more depleted and did not clear differences (solid waste, sewage, human feces, fertilizer, and livestock for -33.6 ± 4.5‰, -34.1 ± 4.8‰, -32.2 ± 3.8‰, -35.0 ± 3.9‰, and -34.9 ± 4.4‰ respectively). These sources were classified into non-traffic source in this study. From March, 2018 to March, 2019, ambient NH3 samples were collected at an urban site in Beijing. With the newly developed source profiles in this study, the contribution of traffic and non-traffic sources to ambient NH3 in an urban site in Beijing was calculated using the 15N isotope mass balance equations. Traffic and non-traffic sources contributed 8% and 92% to ambient NH3 in urban Beijing, respectively. The highest seasonal average contribution of traffic to ambient NH3 was found in winter (22%). Our results reveal the importance of traffic source and provide evidence for the need to control NH3 emission from traffic in urban Beijing in winter.